Numerical simulation of heat and mass transfer in bidispersed capillary structures: Application to the evaporator of a loop heat pipe. (5th June 2016) - Mottet, L.; Prat, M.
Abstract: Heat and mass transfer with phase change in an evaporator unit cell is analysed using a mixed pore network model. Two different kind of wick are investigated: a monoporous capillary structure characterised by a monomodal pore size distribution and a bidispersed capillary structure characterised by a bimodal pore size distribution. The evaporator thermal performance, i.e. the conductance, and the overheating of the casing are compared at different heat loads with experimental results and show a good agreement. For a large range of flux, the bidispersed wick has higher thermal performance than the monoporous wick. A bidispersed wick prevents the overheating of the casing which is the most encountered limit in LHP application. The liquid–vapour phase distribution, as well as the vapour saturation and the vapour mass flow rate are investigated to explain these behaviours.